Multi-omics and network pharmacology reveal Huayu-Tongbi decoction reduced arthritis-related bone erosion - Bozhen Chen; Lu Yang; Houchun Wang; Peng Yu; Mengyang Ma; Meiqi Chen; Yingyan Zhou; Jiaqi Wu; Huasheng Liang; Maojie Wang; Runyue Huang; Yiting He; et al. (Chinese Medicine)
Abstract Background Rheumatoid arthritis (RA), an autoimmune disorder marked by joint inflammation and bone destruction, lacks effective therapies targeting bone erosion. Huayu-Tongbi decoction (HT), a traditional Chinese medicine (TCM) herbal decoction, has been used as a complementary treatment for RA, yet the mechanisms of its active components and multitarget therapeutic effects remain unclear. Materials and methods An adjuvant-induced arthritis (AIA) model was established in rats, and enzyme-linked immunosorbent assay, histopathological staining, and micro–Computed Tomography to assess the effects of HT on joint inflammation and bone erosion. Furthermore, serum pharmacochemistry combined with network pharmacology identified the HT’s active ingredients and targets. In vitro multi-omics study revealed the decoction’s effect and underlying mechanisms in osteoclastic differentiation. Results HT significantly reduced joint inflammation and bone erosion in AIA rats. Serum pharmacochemistry identified 44 absorbed components in HT, and network pharmacology analysis predicted 89 key targets of HT related to RA. In vitro experiments demonstrated that HT inhibited RANKL–induced osteoclastic differentiation through multiple pathways, such as PPAR pathway, AA metabolism, and NF-κB pathway. Conclusion This study confirmed the beneficial effects of HT in experimental arthritis and explored the specific mechanisms involved. HT inhibited osteoclastic differentiation through multiple targets and pathways to reduced bone destructions, providing a potential therapeutic strategy for preventing RA-related bone erosion. Graphical abstract